Analysis of the Akidah Akhlak Textbook to Strengthen Students’ Moral Character and Spiritual Values - Aulia Miratul Afifah; Tumin Tumin; Iskandar Iskandar (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to analyze Islamic Education textbooks on the topic of Akidah Akhlak to see how these books shape students' understanding of the values ​​of faith and morals, and how the material, presentation methods, and relevance of the book's content contribute to the internalization of moral and spiritual values ​​in everyday life. The method used is a qualitative approach with content analysis techniques. The primary data source is the textbook Akidah Akhlak Madrasah Aliyah grade XII. The researcher used several secondary sources, such as scientific journals, similar textbooks at other educational levels, and the results of previous research. The data collection technique is through literature study, namely studying the contents of the book and recording the aspects analyzed. The data analysis technique uses data reduction by sorting relevant information. Then the data presentation is in the form of a description of the findings, and conclusions are drawn. To maintain the validity of the data, source triangulation is carried out by comparing the contents of the book with supporting literature, including the works of international academics such as Abdurrahman Badawi (moral philosophy) and Alasdair MacIntyre (ethics), which provide a broader perspective on the study of faith and morals. The analysis shows that the Akidah Akhlak textbook aligns with the curriculum and provides a strong foundation in faith and moral education, starting from the systematic presentation of material, straightforward language, and legitimate evidence, which has met the BSNP standards. The learning is conceptual and applied, by presenting concrete examples from Islamic scholars and figures who can be used as role models. However, this book is still normative, has limited references, and does not optimally emphasize the development of character and critical thinking skills of students.